2008
DOI: 10.1371/journal.pgen.1000100
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionarily Conserved Sexual Signature in the Primate Brain

Abstract: The question of a potential biological sexual signature in the human brain is a heavily disputed subject. In order to provide further insight into this issue, we used an evolutionary approach to identify genes with sex differences in brain expression level among primates. We reasoned that expression patterns important to uphold key male and female characteristics may be conserved during evolution. We selected cortex for our studies because this specific brain region is responsible for many higher behavioral fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
96
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 42 publications
1
96
1
1
Order By: Relevance
“…Sex-specific patterns of gene expression have been well studied in the literature across many organisms (Yang et al 2006;Ober et al 2008;Reinius et al 2008;Trabzuni et al 2013). However, beyond differences in mean gene expression levels, differences in expression variation may be attributed to interaction effects of genomic variants and both environmental and biological variables, such as sex (Idaghdour and Awadalla 2012).…”
Section: Sex-specific Expression Variation Across the Genomementioning
confidence: 99%
“…Sex-specific patterns of gene expression have been well studied in the literature across many organisms (Yang et al 2006;Ober et al 2008;Reinius et al 2008;Trabzuni et al 2013). However, beyond differences in mean gene expression levels, differences in expression variation may be attributed to interaction effects of genomic variants and both environmental and biological variables, such as sex (Idaghdour and Awadalla 2012).…”
Section: Sex-specific Expression Variation Across the Genomementioning
confidence: 99%
“…Previous studies have indicated that anywhere between 30 and 60% of metazoan genes may be sex biased Parisi et al 2004;Reinke et al 2004;Yang et al 2006;Reinius et al 2008;Small et al 2009;Innocenti and Morrow 2010;Assis et al 2012;Reinius et al 2012;Thomas et al 2012). Genes with sex-biased expression contribute to both somatic and gonadal sexual dimorphisms Parisi et al 2004;Yang et al 2006;Mank et al 2008a;Reinius et al 2008).As the number of X chromosomes differs between males and females, the X plays a large role in the evolution of sexual dimorphisms (Rice 1984;Mank et al 2008a). Due to both sex-specific natural selection and the unique life cycle of the X chromosome, it is predicted that sex-biased genes should accumulate on the X (Rice 1984).…”
mentioning
confidence: 99%
“…1 We hypothesized that the basis of this sex bias is already established in the brain before birth. Here, we show that several genes encoded in the Y-chromosome are expressed in many regions of the male prenatal brain, likely having functional consequences for sex bias during human brain development.…”
mentioning
confidence: 99%
“…These genes are not only expressed in the brain before birth but some of them are also known to have sex differences in adult brain, 1,4 whereas others are expressed during infancy, but reduced later on during their lifetime. 5 Intriguingly, SRY, a well-known determinant of testicle development during midgestation, 6 showed no evidence of expression in any of the brain regions analyzed (Figure 1b, and Supplementary Figure 1), suggesting that the main somatic sex determinants may be different for the brain and gonads during human gestation.…”
mentioning
confidence: 99%
See 1 more Smart Citation